2013
DOI: 10.2522/ptj.20120072
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Behavioral Interventions for Stress Incontinence: Rates, Barriers, and Predictors

Abstract: Adherence to PFM exercises and bladder control strategies for SUI can be high and sustained over time. However, behavioral interventions to help women link exercise to environmental and behavioral cues may only be beneficial over the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 44 publications
2
59
0
Order By: Relevance
“…However, one study of women who had UI after giving birth concluded that the most common reasons provided for not performing the exercises, or stopping the exercise program within six months after giving birth, included: feeling that the exercises were unnecessary if symptoms were no longer present; forgetting to do the exercises; being too busy to do the exercises; feeling that the exercises were not important; not understanding how to do exercises; or experiencing pain when performing the exercises . Other study, factors associated with poor adherence to pelvic floor exercises in women with UUI included insufficient time or trouble remembering to do the exercises …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, one study of women who had UI after giving birth concluded that the most common reasons provided for not performing the exercises, or stopping the exercise program within six months after giving birth, included: feeling that the exercises were unnecessary if symptoms were no longer present; forgetting to do the exercises; being too busy to do the exercises; feeling that the exercises were not important; not understanding how to do exercises; or experiencing pain when performing the exercises . Other study, factors associated with poor adherence to pelvic floor exercises in women with UUI included insufficient time or trouble remembering to do the exercises …”
Section: Discussionmentioning
confidence: 82%
“…Predictors of PFE adherence include demographic variables (age and education level), general physical status, severity of UI, and self‐efficacy for performing the PFE . Prior studies have shown that older age has a modest positive effect on adherence.…”
Section: Introductionmentioning
confidence: 99%
“…The first‐line treatment for SUI is pelvic floor muscle training (PFMT), but there is no clear consensus on whether the training must be supervised . Adherence to PFMT is a key factor in its effectiveness, but many barriers to exercise exist, including forgetting, not prioritising, and not perceiving the benefits of training …”
Section: Introductionmentioning
confidence: 99%
“…19 Current first-line treatment consists of behavioral strategies such as pelvic floor exercises that can be difficult for women to practice effectively without one-on-one training with specialized healthcare practitioners. 1013 Second-line treatments such as anticholinergic medications have side effects that limit their safety and tolerability. 1417 As a result, there is a need for alternate management strategies that are not only effective, but also better tolerated and more accessible.…”
Section: Introductionmentioning
confidence: 99%